2019
DOI: 10.1111/jog.14124
|View full text |Cite
|
Sign up to set email alerts
|

Role of kisspeptin neurons as a GnRH surge generator: Comparative aspects in rodents and non‐rodent mammals

Abstract: Ovulation is an essential phenomenon for reproduction in mammalian females along with follicular growth. It is well established that gonadal function is controlled by the neuroendocrine system called the hypothalamus-pituitary-gonadal (HPG) axis. Gonadotropin-releasing hormone (GnRH) neurons, localized in the hypothalamus, had been considered to be the head in governing the HPG axis for a long time until the discovery of kisspeptin. In females, induction of ovulation and folliculogenesis has been linked to a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 138 publications
1
12
0
Order By: Relevance
“…Importantly, the response of GP64 cells to E2 was opposite to that of GA28 cells, a goat KNDy neuron cell line, whose KISS1 expression was significantly suppressed by E2 treatment [43]. In addition, the GP64 cells showed an expression of kisspeptin and ERα at the The POA/AVPV kisspeptin neurons are indicated to be direct targets of estrogen positive feedback [29,30,35,47,48], which is one of the most important characteristics of the neurons to induce GnRH/LH surge in female mammals. Previous in vivo studies have demonstrated that E2 treatment increased KISS1 expression in AVPV kisspeptin neurons in rodents [28,31].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Importantly, the response of GP64 cells to E2 was opposite to that of GA28 cells, a goat KNDy neuron cell line, whose KISS1 expression was significantly suppressed by E2 treatment [43]. In addition, the GP64 cells showed an expression of kisspeptin and ERα at the The POA/AVPV kisspeptin neurons are indicated to be direct targets of estrogen positive feedback [29,30,35,47,48], which is one of the most important characteristics of the neurons to induce GnRH/LH surge in female mammals. Previous in vivo studies have demonstrated that E2 treatment increased KISS1 expression in AVPV kisspeptin neurons in rodents [28,31].…”
Section: Discussionmentioning
confidence: 94%
“…The number of POA kisspeptin neurons co-expressing c-Fos, a marker for neuronal activation, increased at the time of LH surge in ewes [32], and the high 17βestradiol (E2) treatment increased the number of c-Fos-positive POA kisspeptin neurons in goats and monkeys [22,33]. Thus, the POA/AVPV kisspeptin neurons are assumed to be a direct target of estrogen positive feedback and the central ovulation regulator [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…The kiss-1 gene expresses kisspeptin and may participate in regulating the HPG axis. Extensive evidence indicates that AVPV-kisspeptin neurons regulate the generation of GnRH and the LH surge, and ARC-kisspeptin neurons are involved in the rhythm of the GnRH pulse [50]. Smith et al analysed kiss-1 mRNA expression in the AVPV and ARC in response to E2 and found that E2 could stimulate AVPV kisspeptin neurons and inhibit ARC kisspeptin neurons [51,52].…”
Section: Discussionmentioning
confidence: 99%
“…The kiss-1 gene expresses kisspeptin and may participate in regulating the HPG axis. An abundance of evidence indicates that AVPV-kisspeptin neurons regulate the generation of GnRH and the LH surge, and ARC-kisspeptin neurons are involved in the rhythm of the GnRH pulse [40]. Smith et al analyzed kiss-1 mRNA expression in the AVPV and ARC in response to E2 and found that E2 could stimulate AVPV kisspeptin neurons and inhibit ARC kisspeptin neurons [41,42].…”
Section: Discussionmentioning
confidence: 99%